Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/microorganisms10040833
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Molecular Profiling of the Clinical Isolates of Staphylococcus aureus Causing Bovine Mastitis from India

Abstract: Staphylococcus aureus is an opportunistic bacterium known to cause severe infections in humans and animals. It is one of the major bacteria causing subclinical and clinical mastitis, leading to significant economic losses in livestock industry. In this study, we have isolated and characterized 80 S. aureus clinical isolates from mastitis-infected animals. The analysis of antimicrobial susceptibility, molecular typing, biofilm production and genetic determinants was performed to understand molecular and phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…There are currently few studies focusing on assessing the whole production chain of cheeses from unpasteurized milk [ 4 , 37 , 38 ]. Most studies have focused on the evaluation of S. aureus strains isolated from raw milk from cows with clinical or subclinical mastitis or only in finished products [ 24 , 29 , 39 , 40 , 41 , 42 ]. Nevertheless, estimation of the prevalence and genetic determinants of S. aureus is always important to facilitate the implementation of rational mitigation strategies and to avoid the dissemination of this pathogen through the food chain [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently few studies focusing on assessing the whole production chain of cheeses from unpasteurized milk [ 4 , 37 , 38 ]. Most studies have focused on the evaluation of S. aureus strains isolated from raw milk from cows with clinical or subclinical mastitis or only in finished products [ 24 , 29 , 39 , 40 , 41 , 42 ]. Nevertheless, estimation of the prevalence and genetic determinants of S. aureus is always important to facilitate the implementation of rational mitigation strategies and to avoid the dissemination of this pathogen through the food chain [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mammary gland is susceptible to colonization by other pathogens such as Streptococcus spp., E. coli , and coliform species, leading to parenchymal inflammation and disease. Mastitis can manifest in subclinical and clinical forms, impacting milk characteristics, quality, and sanitation, while also contaminating milking instruments, increasing the risk of zoonosis [ 62 , 63 , 64 , 65 , 75 ].…”
Section: Current Understanding Of Biofilm Formation In Animal Diseasesmentioning
confidence: 99%
“…In a study, it was observed that some isolates of S. aureus from mastitis milk samples of cows were resistant to all antibiotics tested viz, ampicillin, amoxicillin-sulbactam, ceftriaxone, enrofloxacin, methicillin, and penicillin [ 55 ]. Additionally, resistance profiling against various antibiotics revealed that most S. aureus isolates were resistant to multiple antibiotics [ 56 ]. Given that the S. aureus isolates were resistant to more than three antibiotics, they were MDR bacteria.…”
Section: Abr Pathogens In Milk Samples Across Indiamentioning
confidence: 99%
“…In a similar study, the resistance pattern of S. aureus to ampicillin, methicillin, oxacillin, ceftriaxone, rifampicin, vancomycin, amoxiclav, oxytetracycline, erythromycin, nitrofurantoin, cefuroxime, gentamicin, norfloxacin, ciprofloxacin, and levofloxacin was observed in milk of cows and buffaloes [ 58 ]. Milk samples of cows suffering from Staphylococcal mastitis showed resistance against gentamicin, clindamycin, erythromycin, rifampicin, tetracycline, oxacillin, cefoxitin, and teicoplanin [ 56 ]. The above resistance patterns indicate the resistance of S. aureus to several antibiotics over the years.…”
Section: Abr Pathogens In Milk Samples Across Indiamentioning
confidence: 99%